PENERAPAN MODEL PEMBELAJARAN INQUIRY BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS VII PADA MATA PELAJARAN IPS DI MTS AL-AMIN KAHU KABUPATEN BONE - Nurwahida; Syarifah Balkis; Muhammad Zulfadli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine: 1) Description of the application of the Inquiry Based Learning model in improving students' critical thinking skills, 2) student involvement in the application of Inquiry-Based Learning, and 3) the application of the Inquiry-Based Learning learning process model in improving students' critical thinking skills.The results of the study indicate that: 1) The description of the application of the Inquiry Based Learning learning model is carried out through the stages of orientation, problem formulation, hypothesis formulation, data collection, hypothesis testing, and drawing conclusions, which are able to create active, dynamic, and student-centered learning and improve critical thinking skills which include the ability to explain, analyze, evaluate, and conclude. 2) Student engagement in learning increases through discussion, observation, and presentation activities, although obstacles remain, such as differences in ability, lack of self-confidence, and uneven participation within groups. 3) The Inquiry-Based Learning process has been proven to actual improve students' critical thinking skills, from the initial basic stage to more developed aspects of logistics, evaluation, and conclusion drawing.